KEARIFAN LOKAL PELA DARAH ANTARA DESA SOHUWE DAN DESA LUMAPELU SEBAGAI TANDA PERDAMAIAN MASYARAKAT DI SERAM BAGIAN BARAT - Elvi Yoan Paisina; Sukadari; Sunarti (Program Magister Pendidikan IPS UPY, 2025)
This study aims to examine the local wisdom of Pela Darah (blood oath) between Sohuwe and Lumapelu Villages in West Seram Regency, a symbol of peace and brotherhood between the two communities. Pela Darah is a traditional bond formed through a blood oath between two villages to protect each other, maintain harmony, and prevent conflict. This tradition embodies noble values ​​such as unity,solidarity,and shared responsibility,which are passed down through generations.In a socio-cultural context, Pela Darah serves as an important tool for strengthening community identity and building sustainable peace in areas that have experienced social tension. The research methodology used was a qualitative approach with descriptive methods. Data were obtained through in-depth interviews with traditional leaders, community leaders, and village officials, as well as direct observation of the Pela Darah traditional procession. Furthermore, a literature review was conducted to strengthen understanding of the history and philosophical meaning of this tradition. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that Pela Darah plays a strategic role in maintaining peace between the communities of Sohuwe and Lumapelu Villages. This customary bond serves as a mechanism for conflict resolution, strengthening social relations, and preserving local cultural values. This tradition also encourages cooperation in the social, economic, and security sectors. Revitalizing Pela Darah through the support of traditional leaders and the local government is considered crucial to ensuring the preservation of these noble values ​​and the foundation for building a harmonious and peaceful society. Keywords: Pela Darah, Peace, West Seram